THE EFFECTIVENESS OF OSTENSIVE MEANS METHOD TO IMPROVE STUDENTS’ VOCABULARY MASTERY IN LEARNING ENGLIS AT VII GRADE IN SMPN 4 MALILI - Jhesica; Erwin Akib; Awalia Azis (English Language Teaching Methodology, 2021)
This study aimed to determine the effectiveness of students in learning vocabulary mastery after using the ostensive means that in the process of teaching and learning vocabulary, teachers can bring real objects according to the theme of lessons. This research focuses to noun (things at home, part of body, animal, and fruits). The researcher used the pre-xperimental method, consist of pre-test treatment, and post-test design, and collected the data by giving pre-test and posttest. The sample of the research was class VII SMPN 4 Malili which was 25 students. The sample that researcher used was purposive sampling technique. The result of the research was score in the pre-test was 41, and in the post-test was 75,44. In this research also show that The value t-test was higher than the value of the t-table (27,04>1.713 ). It mean that the alternative hypothesis (H1) was accepted and the null hypothesis (H0) was rejected. It was concluded the implementation of ostensive means in VII grade of SMP Negeri 4 Malili was effective to improve students’ vocabulary mastery consist noun